KELAYAKAN INVESTASI INSTALASI SEA WATER REVERSE OSMOSIS (SWRO) DI KAWASAN WISATA PANTAI KENJERAN SURABAYA - Lokajaya, I Nyoman (Heuristic, 2016)
To make Kenjeran coastal areas as the mainstay tourism Surabaya municipal administration, provision of clean water is one of the means that must be provided. Construction of sea water purification unit with sea water reverse osmosis method is one solution that can be done. This study aims to assess the feasibility of building a water purifier sea with sea water reverse osmosis method. Finally found that for an interval of 15 years at an average rate of visitor arrivals tourist attraction as much as 7,935 people / day needed clean water supply as much as 257.09 m3 / day, equivalent to 10.71 m3 / hour. Average investment value of Rp. 5.5 billion with 19:38% IRR rate much higher than bank interest, which is 10%. Break Even Point investment occurred in year 7 in 2023. Keywords: investment feasibility, Sea Water Reverse Osmosis, coastel tourism area